TINJAUAN HUKUM ISLAM PADA PENYERAHAN PERABOT RUMAH TANGGA DALAM PERNIKAHAN MENURUT TRADISI DI DESA KALIANYAR KECAMATAN WONOSALAM KABUPATEN DEMAK - Gumilar, Purnawan Cahya; Baehaqi, B; Isfihani, I (AL HUKMU: Journal of Islamic Law and Economics, 2023)
Marriage is one of the many religious rituals performed with the aim of creating a family. In rural societies with traditions, marriage is not only performed by means or regulations in accordance with religious decrees. Islam values and exalts a woman's position as an honorable and noble being , by giving her the right to receive dowry. The dowry is only given by the man to the woman he is going to marry, not to anyone else, even if the person is very close to him, and the dowry should not be used by anyone else even by his own husband . Based on this, the author formulates a problem in the research on How to Implement the Tradition of Handing Over Household Furniture at Marriage in Kalianyar Village, Wonosalam District, Demak Regency. This research method is qualitative field research with a research location in Kalianyar Village , Wonosalam District, Demak Regency. The results of this study concluded that the implementation of the tradition of handing over household furniture at weddings in Kalianyar village has been known and carried out for generations. The implication of the study is that in a wedding procession should not burden the man or bride.